Questioning the historicity of Jesus: why a philosophical analysis elucidates the historical discourse - Lataster, Raphael (Value inquiry book series, 2019)
Intro -- Questioning the Historicity of Jesus: Why A Philosophical Analysis Elucidates the Historical Discourse -- Copyright -- Contents -- Foreword -- Acknowledgments -- Introduction -- 1 Which Jesus? -- 2 A Debate among Atheists -- 3 The Problem -- 4 The Philosopher's Probabilistic Approach -- Part 1: The Case for Historicity -- 1 Ehrman's Dual Approach towards the Gospels -- 1 A (Mostly) Wonderful Start -- 2 The Gospels and the Folly of the Hypothetical Source -- 2 Beyond the Gospels -- 1 The Problem of Paul -- 3 Casey's Superfluous 'Scholarship' -- 1 Poisoning the Well -- 2 'Method' -- 3 Why the Gospels Ought to Be Trusted, but Only When We Feel like It -- 4 After the Case -- 5 Even Worse than Ehrman: Offensive and Facetious -- 6 Crossan's Brief Attempt -- Part 2: The Case for Agnosticism -- 4 Inadequate Methods -- 1 History Concerns What Probably Happened -- 2 Criteria for Authenticity -- 3 Faith and Inconsistency -- 4 A Bayesian Alternative -- 5 The Criteria vs. Bayes -- 5 Inadequate Sources -- 1 The Silence of the Primary Sources -- 2 'Other' Christian Sources -- 3 (Non-Christian) Extrabiblical Sources -- 4 Josephus -- 5 Tacitus -- 6 Thallus (and Phlegon) -- 7 Pliny, Suetonius, and Mara bar Serapion -- 8 The Talmud -- 9 The Less Interesting Books of the New Testament -- 10 The Canonical Gospels: Matthew, Mark, Luke-Acts, and John -- 11 Mark's Burden -- 12 The Genre of the Gospels -- 13 Burridge's Take on the Gospels' Genre -- 14 Mark's Failure -- 6 The Problems of Paul -- 1 The Docetic/Marcionite Jesus -- 2 The Earliest Witness' Sources -- 3 Paul's Minimal, Unquotable Jesus -- 4 Paul's Cosmic Christ -- 5 Philo's Pre-Christian and Pre-Pauline 'Celestial Jesus' -- 6 The Evolution of Jesus -- 7 Fictitious Founders -- 8 The Revelation of/from Paul -- 9 Agnosticism is Rational -- Part 3: The Case for Mythicism -- 7 Prior Probabilities.